Additive effects and safety of fixed combination therapy with 1% brinzolamide and 0.5% timolol versus 1% dorzolamide and 0.5% timolol in prostaglandin‐treated glaucoma patients. Issue 8 (3rd April 2017) - Aihara, Makoto; Adachi, Misato; Matsuo, Hiroshi; Togano, Tetsuya; Fukuchi, Takeo; Sasaki, Noriyuki; ,
Abstract: Purpose: To compare the additive effects and safety of 1% brinzolamide/0.5% timolol fixed combination (BTFC) versus the low‐dose regimen of 1% dorzolamide/0.5% timolol fixed combination (DTFC) in patients with open‐angle glaucoma and ocular hypertension (OAG/OH) following treatment with prostaglandin analogues (PGAs). Methods: A prospective, randomized, double‐masked, multicentre, parallel‐group and active‐controlled study included 201 Japanese OAG/OH patients who had been treated with PGA. Efficacy was assessed as the change in intra‐ocular pressure (IOP) from baseline after weeks 4 and 8. Safety was assessed with adverse event rates, ocular discomfort score, blur scale, blood pressure and heart rates, best‐corrected visual acuity (BCVA) and slit lamp examinations. Results: Intra‐ocular pressure (IOP) change from baseline at 9 AM/11 AM pooled over the 8 weeks was −3.3/−3.3 mmHg in the BTFC group and −2.9/−3.4 mmHg in the DTFC group, demonstrating non‐inferiority of BTFC to DTFC. Ocular irritation was frequently seen in DTFC group. Although blurred vision was frequently seen in BTFC group, it was transient and blurring became the equivalent 3 min after instillation between two groups. No noteworthy issue was observed in other safety outcome. Conclusion: Non‐inferiority of BTFC to DTFC in IOP reduction was demonstrated after adding onto PGA therapy in Japanese OAG/OH patients. Although the score of blurred vision was transiently higher in BTFC than DTFC, treatment difference decreased and disappeared with time. Thus, BTFC can be considered as a safe and effective agent for glaucoma treatment.